Safety and efficacy of aluminosilicate of sodium, potassium, calcium and magnesium as a feed additive for pigs. (14th June 2019) - ; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Durjava, Mojca Kos; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on aluminosilicate of sodium, potassium, calcium and magnesium as a feed additive for pigs. The additive, that contains at least 66% of aluminosilicate of sodium, potassium, calcium and magnesium as main component, is intended for use as a technological additive (functional groups: (i) anticaking agents) in premixtures and feedingstuffs for pigs at a maximum inclusion level of 30, 000 mg/kg. In the absence of data, the FEEDAP Panel could not conclude on the safety of the additive for the target species and the users. The additive is considered safe for the consumer and the environment at the proposed conditions of use. The additive has the potential to act as an anticaking agent in complete feed of pigs at a concentration of 30, 000 mg/kg feed.